Systematic Literature Review: Pengaruh Sistem Penerimaan Peserta Didik Baru Berbasis Tes terhadap Adaptabilitas dan Pemenuhan Standar Kompetensi Peserta Didik SMA di Kecamatan Kebayoran Baru - Sep Arinda Risa Kamal; Nurhattati Nurhattati; Kamaludin Kamaludin (Journal on Education, 2025)
This study aims to analyze the impact of a test-based New Student Admission (PPDB) system on student adaptability and the fulfillment of competency standards at the senior high school (SMA) level in Kebayoran Baru District. The study is motivated by the differing effectiveness between the currently dominant zoning system and a test-based academic selection system, particularly in fostering a conducive learning environment and enhancing the quality of education. Employing a quantitative research design, data will be collected through questionnaires and documentation from high school students in the region. Descriptive and inferential statistical analyses will be used to measure the effects of the test-based system on students' learning outcomes, motivation, and engagement. The findings of this study are expected to provide a comprehensive understanding of the test-based selection system's impact on educational quality and offer policy recommendations that balance equity and learning effectiveness.